SOCIAL SCIENCES EDUCATION: EXPLORING THE OCEAN OF SOCIAL KNOWLEDGE - Syarifuddin; Rani Noeraeni; Indah Sulistiani; Loso Judijanto; Muh. Dzihab Aminudin S (Adisam Publisher, 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing social studies education: diving into the ocean of social knowledge. Delving into the growing field of social knowledge that can spur a new way of human life, from the beginning of life to its end are interrelated, this review synthesizes existing research, identifies trends, and offers insights for educators, policy makers, and researchers . The reason behind this exploration lies in the urgency to find out the scope of social knowledge in the world of education, namely: replacing the role of humans, namely by automating a task or process. Strengthening the human role, namely presenting information, tasks, or processes. Restructuring or making changes to a task or process. This review covers various aspects, starting from the scope of social studies education, learning theories of social studies education and social studies education in the school curriculum. By examining the interaction between educational and social aspects, this literature review contributes to the ongoing discourse regarding social studies studying, examining, and assessing human life systems on the surface of the earth in their social context or humans as members of society.